Covid-19 Pandemic and Optimal Debt-to-GDP Ratio Threshold in Sub-Saharan Africa - Jonathan Oniore; Oghenebrume David Akatugba (Journal La Sociale, 2022)
The empirical data on the effect of a high debt-to-GDP ratio on economic growth is conflicting. The article used the GDP Indicator to investigate the trajectory in the debt-to-GDP ratio in 45 nations in Sub-Saharan Africa during the COVID-19 Pandemic and to determine whether there is a point at which public debt becomes damaging to the region's economy. The major results demonstrated that as long as the economies of Sub-Saharan Africa continue to expand, a high debt-to-GDP ratio is not always negative; in fact, the majority of nations with a debt-to-GDP ratio greater than the 77 percent threshold had increased economic growth. Additionally, the paper discovered that countries in the region may face a high debt-to-GDP ratio as a result of excessive spending prompted by the Covid-19 pandemic, as well as an unpredictable slowdown in economic activity as a result of movement restriction policies imposed by subregional governments. Another intriguing conclusion is that Sub-Saharan Africa's average debt-to-GDP ratio of 56.6 percent in 2020 is much lower than the suggested limit of 77 percent. However, the report advised that governments reduce wasteful spending without jeopardizing the region's economic development rate. Finally, fiscal policies should be accompanied by monetary policies to promote effective public investment, simplified tax expenditures, increased public financial management, and better debt management and transparency.